2022
DOI: 10.3390/pr10071424
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Microstructural Properties of Composite Mortars with Lime, Silica Fume and Rice Husk Ash

Abstract: A mixture of hydraulic lime and pozzolanic material can be used as a binder in making concrete and mortar for energy-efficient construction purposes. Generally, lime possesses lower strength and higher setting time. By introducing pozzolans in the lime mortar, their cementitious properties could be increased and could compete with the cement mortars. The use of pozzolan-lime binder in mortar reduces the utilisation of cement, and hence reduces the environmental problem originating from cement production. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Based on the XRD results, it is observed that the obtained silica structure is generally amorphous, which is related to the rapid condensation of volatile silica and surface tension silicon in the phase transition 27 . The broad peak obtained at an angle of about 22° indicates amorphous silica with nanometer size, and this result was compared with similar articles, which all showed the same result 28,29 …”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Based on the XRD results, it is observed that the obtained silica structure is generally amorphous, which is related to the rapid condensation of volatile silica and surface tension silicon in the phase transition 27 . The broad peak obtained at an angle of about 22° indicates amorphous silica with nanometer size, and this result was compared with similar articles, which all showed the same result 28,29 …”
Section: Resultsmentioning
confidence: 68%
“…27 The broad peak obtained at an angle of about 22 indicates amorphous silica with nanometer size, and this result was compared with similar articles, which all showed the same result. 28,29 F I G U R E 1 The size distribution of synthesized silica particles in, (A) 250,000, (B) 150,000 times magnifications.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Similar conclusion was also drawn in a study where the density of RHA concrete found same for all replacement level (Ephraim et al, 2012). Lime based concrete also exhibited the (Malathy et al, 2022). However, some contradictions in the results were also noticed due to fact that there are various types of lime and their properties differ significantly.…”
Section: Density Testmentioning
confidence: 88%
“…The scale range used in the SEM analysis was 5 µm with the resolution of 5000x. The samples were examined in the SEM instrument [ 46 , 47 , 48 , 49 , 50 ]. After the flexural strength test, mortar bonded with the fabrics was taken out from the ferrocement composites.…”
Section: Methodsmentioning
confidence: 99%